Treatment results of children with the diagnosis of acute myeloid leukemia. Is trisomy 21 an important cause of mortality? - Sarbay, Hakan; Gundogdu, Muge; Atay, Avni; Malbora, Baris (International Journal of Contemporary Pediatrics, 2023)
Background: Acute myeloid leukemia (AML) is the second most common leukemia accounts for 20% of childhood leukemia. Intensive chemotherapy and hematopoietic stem cell transplantation (HSCT) improve outcomes. In this study, it was aimed to present the clinical features and treatment results of patients diagnosed with pediatric AML in the last three years. Methods: It is an observational clinical study, patients who received chemotherapy and HSCT with the diagnosis of AML between 2018 and 2020 were retrospectively evaluated. Age, gender, AML subtype, genetic characteristics, laboratory findings, treatment responses, febrile neutropenia and fungal infection frequencies of the patients were evaluated. HSCT indications, pre-transplant bone marrow aspiration results, transplant type, donor characteristics, and post-transplant complications of patients who underwent HSCT were recorded. Post-treatment status and treatment success rates of the patients were evaluated. Results: Of the 46 patients included in the study, 26 were female and 20 were male. The mean age was 8.2 ± 5.75 years. The most common subtypes were AML M4 and M5 with 9 patients. Total of 201 febrile neutropenia attacks were observed. Suspicious or definite proven Aspergillus infection was detected in 20 of the patients. HSCT was applied to 27 of the patients. Four patients were Down syndrome-myeloid leukemia (DS-ML) and FLT3-ITD mutation was detecetd in 5 patients. Conclusions: FLT3-ITD mutation, relapse disease, and pre-HSCT M2 bone marrow were found to be highly correlated with progressive disease and mortality. In addition, patients with Down syndrome had a high mortality due to additional comorbidity and drug adverse effects.